1988
DOI: 10.1016/0378-1097(88)90372-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of NADH- and NADPH-linked acetoacetyl-CoA reductases in the poly-3-hydroxybutyrate synthesizing organism Alcaligenes eutrophus

Abstract: Two constitutive acetoacetyl‐CoA (AcAc‐CoA) reductases were purified from Alcaligenes eutrophus. Incorporation of [1‐14C]‐acetyl‐CoA into poly‐3‐hydroxybutyrate (PHB) by systems reconstituted from purified preparations of either 3‐ketothiolase, AcAc‐CoA reductase and PHB synthase, occurred only when NADPH‐AcAc‐CoA reductase was present. The NADH reductase was active with all of the d(−)‐ and l(+)‐3‐hydroxyacyl‐CoA substrates tested (C4‐C10), whereas the NADPH reductase was only active with d(−)‐3‐hydroxyacyl‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
98
0
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 12 publications
6
98
0
3
Order By: Relevance
“…The K m for acetoacetyl-CoA determined for the 3-hydroxybutyryl-CoA dehydrogenase of D. biacutus was 18 M, similar to those found for the same enzyme in other PHB-forming bacteria (8,18,29,31). This enzyme, together with the detected 3-enoyl-CoA hydratase (crotonase), is presumably involved in PHB synthesis.…”
supporting
confidence: 77%
“…The K m for acetoacetyl-CoA determined for the 3-hydroxybutyryl-CoA dehydrogenase of D. biacutus was 18 M, similar to those found for the same enzyme in other PHB-forming bacteria (8,18,29,31). This enzyme, together with the detected 3-enoyl-CoA hydratase (crotonase), is presumably involved in PHB synthesis.…”
supporting
confidence: 77%
“…Lysates were stored on ice while the experiments were conducted. Reductase activity obtained with the use of either NADPH or NADH as the cofactor was measured at pH 6 and 25°C using the published protocol (10). The assay reaction mixtures contained 50 mM potassium phosphate buffer, 0.1 mM NADPH or NADH, and 32 M acetoacetyl-CoA.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen other potential isologs were also found to encode amino acid sequences that could potentially indicate acetoacetyl-CoA reductase activity (29). The roles of the newly discovered genes in PHB biosynthesis were unclear, especially given the results of an earlier biochemical study that suggested there was a single NADPH-dependent acetoacetyl-CoA reductase in R. eutropha (10). In order to determine the roles of the reductase genes in R. eutropha, we deleted phaB1, phaB2, and phaB3 from the genome both individually and in combination.…”
mentioning
confidence: 99%
“…The phenotype of this mutant class was referred to as PHB-leaky. PHB-leaky mutants exhibited activities of all three PHBbiosynthetic enzymes; there was also no evidence that isoenzymes of the biosynthetic P-ketothiolase (25) or of the acetoacetyl coenzyme A reductase (26) were affected in these mutants. Measurements with reconstituted enzyme 5844 PRIES ET AL.…”
mentioning
confidence: 91%